Perubahan Luas Penutupan Padang Lamun Di Kepulauan Seribu, DKI Jakarta - Kawaroe, Mujizat; Jaya, Indra; S., Indarto H.; Sari, Dahlia Wulan; W., Sundari Wening (Universitas Atma Jaya Yogyakarta, 2010)
Seagrass is one of productive and economical marine ecosystem, but recently there are indications that this area is decreasing and every kind of damage is happening. The research was conducted to reveal the change of seagrass width area and to determine the suitable location for donor and acceptor of seagrass transplantation. Methods of research were collecting and analyzing the satellite image of the research location, bathymetri mapping and water quality parameter, and also determining environment charasteristics that suitable to be performed by counting Seagrass Transplantation Suitability Index (STSI). The results show that in year 1999-2004, the derivation area of seagrass was 678.300 m2. Pari island has depth range between 0-50 metres and the physics and chemical parameter of water have a good range where the seagrass can live. According to the analysis result of STSI, suitable areas for seagrass transplantation donor is station no. 5 and 6 for seagrass species of Enhalus acoroides and station no. 2 and 7 for seagrass species Thalassia hemprichii. The implication of this research is that the seagrass needs rehabilitation to overcome seagrass ecosystem for better condition.